Are we still neglecting neglect? Thermal injury. (4th April 2011) - Kemp, A; Jones, S; Potokar, T; Debelle, G; Curtis, E; Maguire, S
Abstract : Background: 63% of all childhood thermal injuries affect children under 3 years old and many would advocate that they represent an element of neglect, 'failure to protect a child from physical, harm or danger, to ensure adequate supervision, access to appropriate medical care or treatment'. This study explores factors associated with thermal injury to identify possible indicators of childhood neglect. Methods: Data regarding markers of possible neglect were collected from children <16 years attending five ED's and three inpatient burns-units over 20 months namely: failure to supervise, lack of first aid, >24 h to presentation for children with a partial-thickness-burn or worse (significant burn), known to social services. Cases referred to child protection services were compared with those that were not. Results: 1031 cases included in the study, 82%(846) had a superficial-partial-thickness burn or worse, late presentation: 24% (203/846) presented > 24 h post injury. lack of supervision: 23.5% of children were unsupervised at the time of injury. First aid: 25.5% received no, inadequate or detrimental first aid in the home, 12.6% were known to social services. Regarding the number of risk factors in each child with a significant burn: 39% had one, 29% had two 11% had three and 13.6% had four risk factors. 104 cases were referred to child protection services. With the exception of injury severity and 'known to social services' there was no significant difference in the number or nature of risk factors or age group between those referred and those not. 4/104 cases of abuse were substantiated. Conclusions: This study shows that there is no difference between the markers of possible neglect between children referred to CP services and those that are not. We would advocate that all of these children need some degree of secondary prevention. A needs-assessment tool could be administered in EDs to identify three groups of young children who (1) those who need simple injury prevention advice, (2) those who require additional prevention advice on appropriate first aid/supervision etc. (3) those who have multiple needs and may require assessment for a child-in-need or child protection assessment.